LEGAL SCIENCE IN THE CONDITIONS OF MODERN CHALLENGES AND THREATS - Корчак, Наталія Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to highlight the importance of legal science in the life of Ukrainian society in face of modern challenges and threats. Methods: analysis, synthesis, induction, deduction, abstraction, concretization, generalization. Results: author’s conclusions about the need to revise the worldview base of scientific research within the concept of legal science. Discussion: underestimation of the role of legal science, role and lack of proper justification of public administration reforms have negatively affected the current state of lawmaking and law enforcement. Legal science is a type of cognitive activity and a powerful element of the organizational and legal mechanism of management. Increasing the level of theoretical and legal research, the disclosure of the deep patterns of legal regulation are inextricably linked with the solution of specific practical problems. Politicization, lack of new legal paradigms, focus only on modernization of legislation, underestimation of potential categories of legal understanding to solve practical problems of social transformation and awareness the realities of legal reality, growing tendencies to legal nihilism and legal idealism, low innovative potential and research basis, point to weaknesses of modern legal science. These are the challenges and at the same time threats, overcoming of which requires a revision of the worldview base of scientific research, development and adoption at the state level of a scientifically sound concept of its own development. Modern domestic legal science should: 1) become the foundation of lawmaking and law enforcement in terms of scientific justification, expediency and effectiveness, study and generalization; 2) ensure systemic, balanced and internal coherence of legislation.